Communication of corporate social responsibility (CSR) on corporate websites : Lessons from the world’s largest car manufacturers - Laakio, Salli (fi=Turun yliopisto|en=University of Turku|, 2018)
The main focus of this study is on CSR online communication, text and pictures. The purpose of the study is to examine how do companies communicate their CSR practices on their corporate websites. This research question is further divided to three sub questions: (1) Where and how is the CSR information visually presented on the corporate websites? (2) What kind of communication tactics are used on the corporate websites? (3) What is the affective dimension of communication on corporate websites? Attention for the social and environmental impacts of international business is not a new phenomenon. During past years, renewed interest has risen, due to global problems. Companies are increasingly called upon to contribute in a positive way, and to drive their actions forward towards a more sustainable development. Although other studies considering CSR online communication have been conducted, the frame of reference of these studies has emphasized the groups the communication is aimed to and if the focus was on the way of communicating the CSR information, the analysis has been conducted with a comparative approach rather than a descriptive one. This study aims to fill this research gap. The theoretical framework of the study is based on a framework conducted by Du & Vieira (2012) which identifies three different specific characteristics used in CSR online communication on corporate websites. The framework describes that a number of framing mechanisms that enhance the salience and effectiveness of CSR messages, communication tactics that boost the credibility of CSR messages, and an affective dimension of communication, which was mostly story-based are utilized in the CSR communication of oil companies on their websites. This study was conducted as a case study. The case companies were selected amongst the automotive industry, namely the 6 largest car manufacturing companies globally. The data in this study was gathered from the official global corporate websites of the case corporations. When the websites had been identified, stage 2 was to browse through the website to identify framing mechanisms, step three included coding and analysing of the text content of the websites. The fourth step of the analysis first combined the analysis results received from steps 2 and 3 into a sensible ensemble for each company. After this, the results for each company were drawn to the theoretical framework and study objectives. The study concludes that the characteristics of CSR communication identified by Du & Vieira (2012) could be detected in the CSR online communication in the case companies presented in this study, with a few weaker exceptions. Due to the nature of a case study, the findings of this thesis are not universally applicable information. In order to create generalizations about the phenomenon it would be useful to conduct a multiple case study with more than one industry represented related to the ways in which companies communicate about their CSR practices on their corporate websites.